(untitled) (University of Khartoum Engineering Journal, 2022)
Property tables are not suitable for sensitivity and optimisation analysis of complex thermodynamic systems that require the thermodynamic properties to be repetitively determinated at a large number of points in the system. This paper shows how Microsoft Excel can be used to develop computerised tables that automate the evaluation of thermodynamic properties. The property tables were copied in Excel and Visual Basic for Applications (VBA) was used to develop a number of user-defined functions that automate the interpolation of thermodynamic data. While maintaining the use of thermodynamic tables, which is an important educational process, the computerised tables can be a useful teaching aid that helps students to have better understanding of thermodynamics. The usefulness of the computerised tables is demonstrated by analysing the gas-turbine cycle with intercooling reheating and regeneration. Using the exact variable-specific heat method, the cycle was analysed for the effects of the inter-stage pressures on the plant’s thermal efficiency and net specific-work. The paper shows that more accurate estimates of the optimum values of these pressures could be obtained than usually given by the widely adopted approximate constant-specific heat method. The Excel-based tables are particularly useful in developing countries like Sudan, where dedicated educational software is lacking.